The Educational System in Israel – Changes in Perception and Approaches since the Late 19th Century - Liviatan, Sarit Albaldes (Biuletyn Historii Wychowania, 2015)
Education, by its very nature, is an institution that preserves tradition and its values, and thus preserves structures, patterns and processes that have become rooted in society and continue to influence and shape it. Education was one of the significant forces in the shaping of modern culture and the modern social cohesion of the Jewish people along with the peoples of Europe from the end of the 19th century and throughout the entire process of its renewed hold over its land. In the period that preceded the establishment of the State the focuses of power were distributed politically, with the considerable involvement of the community in what was done in education. Since the establishment of the State, the structure of the shaping of education policy in Israel has experienced changes. The principle of statehood guided Prime Minister Ben-Gurion, who sought to apply it also to the educational system. For many years since the establishment of the State, changes have been made in the national consensus about the emphasis of values, according to the spirit of the era and the major events that occurred in the country and society in Israel. In the transition to the 21st century, Israeli society is undergoing major changes that have direct implications on the positioning of formal education in society and on the image of the desired graduate.